2009
DOI: 10.1074/jbc.m109.026674
|View full text |Cite
|
Sign up to set email alerts
|

Endosomal Endothelin-converting Enzyme-1

Abstract: Neuropeptide signaling at the cell surface is regulated by metalloendopeptidases, which degrade peptides in the extracellular fluid, and ␤-arrestins, which interact with G protein-coupled receptors (GPCRs) to mediate desensitization. ␤-Arrestins also recruit GPCRs and mitogen-activated protein kinases to endosomes to allow internalized receptors to continue signaling, but the mechanisms regulating endosomal signaling are unknown. We report that endothelin-converting enzyme-1 (ECE-1) degrades substance P (SP) i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
29
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 58 publications
(29 citation statements)
references
References 50 publications
0
29
0
Order By: Relevance
“…With respect to these, it is interesting to remark that a member of M13 family (ECE-1) localizes into the luminal side of endosomal membrane where it degrades interna lized neuropeptides (e.g., substance P, apelin-13) (El Messari et al , 2004 ;Cottrell et al , 2009 ), suggesting their possible biological relevance as substrates of this type of enzymes. As a matter of fact, besides the classical involvement of neuropeptides in neurotransmission and vasal smooth muscle cells constriction, at least for some of them, a novel role in the modulation of immune responses has been envisaged (Skidgel et al , 1984 ;Johnson et al , 1999 ;Marriott and Bost , 2001 ;Yaraee et al , 2007 ), affecting proinfl ammatory cytokine and chemokine activation (in the case of apelin-13) and macrophage activation (in the case of the substance P) in the early phases of immune responses to Salmonella infection (Kincy -Cain and Bost, 1996 ;O ' Connor et al, 2004 ;Leeper et al , 2009 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…With respect to these, it is interesting to remark that a member of M13 family (ECE-1) localizes into the luminal side of endosomal membrane where it degrades interna lized neuropeptides (e.g., substance P, apelin-13) (El Messari et al , 2004 ;Cottrell et al , 2009 ), suggesting their possible biological relevance as substrates of this type of enzymes. As a matter of fact, besides the classical involvement of neuropeptides in neurotransmission and vasal smooth muscle cells constriction, at least for some of them, a novel role in the modulation of immune responses has been envisaged (Skidgel et al , 1984 ;Johnson et al , 1999 ;Marriott and Bost , 2001 ;Yaraee et al , 2007 ), affecting proinfl ammatory cytokine and chemokine activation (in the case of apelin-13) and macrophage activation (in the case of the substance P) in the early phases of immune responses to Salmonella infection (Kincy -Cain and Bost, 1996 ;O ' Connor et al, 2004 ;Leeper et al , 2009 ).…”
Section: Discussionmentioning
confidence: 99%
“…In this respect, it is noteworthy that degradation of neuropeptides by ECE-1 in endosomes under acidic conditions (i.e., pH 5.5) is documented (Fahnoe et al, 2000) and it is associated to intracellular signaling and receptor turnover (El Messari et al , 2004 ;Roostermann et al, 2007;Cottrell et al , 2009 ); analogously, we found that Zmp1 optimum activity toward the synthetic substrate is at pH 6.3 (Figure 2A), a value corresponding to that of the early endosome (Pethe et al , 2004 ). Therefore, it might be speculated that, similarly to ECE-1, Zmp1 operates within the phagosome, arresting its maturation (Master et al , 2008 ;Johansen et al , 2011 ).…”
Section: Discussionmentioning
confidence: 99%
“…Although fluorescent CCK or gastrin remained trapped in endocytosic vesicles over times as long as 6 h, we do not know if the peptidic ligands were still intact and bound to internalized CCK2R at these times or if they were degraded by proteases. Other studies have shown that substance P, calcitonin gene-related peptide, and somatostatin are degraded in acidified early endosomes following internalization with their cognate receptors (32). Interestingly, it was suggested that retention of ligand integrity or ligand degradation may impact signaling triggered by internalized GPCR (33).…”
Section: Discussionmentioning
confidence: 99%
“…Endothelin-converting enzyme-1 degrades substance P and calcitonin gene-related peptide in acidified endosomes to disrupt the ligand-GPCR-␤-arrestin complex, which promotes ␤-arrestin return to the cytosol and receptor recycling to the plasma membrane (47,48). This mechanism also attenuates substance P-induced ERK activation (35). Although the ligand for PAR 2 is tethered to the receptor, other endosomal proteases may degrade the ligand to disrupt the PAR 2 -␤-arrestin-MAPK complex and thereby attenuate ERK signaling.…”
Section: Expression Of Catalytically Inactive Amsh or Ubpy Does Not Pmentioning
confidence: 99%